2015
DOI: 10.4269/ajtmh.14-0509
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis in Israeli Travelers

Abstract: Abstract. Histoplasmosis is a common endemic human mycoses acquired mostly in the Americas. We reviewed 23 cases of histoplasmosis in Israeli travelers; 22 had traveled to Central or South America and one to North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
(21 reference statements)
0
8
0
1
Order By: Relevance
“…This systematic review of diagnoses of histoplasmosis made in Europe and Israel over 16 years identified 728 cases. Of those, 505 were described in five retrospective studies, including three studies of acute histoplasmosis in travellers diagnosed in Spain [13], Italy [15], and Israel [16]; one study of imported AIDS-related histoplasmosis conducted by the French National Reference Centre for Mycoses and Antifungals (NRCMA) [14]; and one summarising imported endemic mycoses (including histoplasmosis) in hospitalised patients in Spain [12]. The remaining 223 cases were retrieved from single case reports or small case series .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review of diagnoses of histoplasmosis made in Europe and Israel over 16 years identified 728 cases. Of those, 505 were described in five retrospective studies, including three studies of acute histoplasmosis in travellers diagnosed in Spain [13], Italy [15], and Israel [16]; one study of imported AIDS-related histoplasmosis conducted by the French National Reference Centre for Mycoses and Antifungals (NRCMA) [14]; and one summarising imported endemic mycoses (including histoplasmosis) in hospitalised patients in Spain [12]. The remaining 223 cases were retrieved from single case reports or small case series .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, five studies involving 505 subjects (295/436 males, 67.7%) described cumulative experiences of histoplasmosis: two from Spain (one regarding imported endemic mycoses from 1997 to 2014 [12], the other relating to histoplasmosis in Spanish travellers to Latin America [13]), a retrospective study from metropolitan France reporting all the cases of histoplasmosis in PLWH diagnosed between 1985 and 2006 [14], and two about cases of acute histoplasmosis diagnosed in travellers in a single centre in Italy between 2005 and 2015 [15] and in Israel between 2000 and 2012 [16].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Since the risk of Histoplasma exposure in Europe is minimal, patients, who present with dyspnea, fever and malaise are not primarily considered for diagnosis of histoplasmosis. Remarkably however, in the recent series from Israel all cases of histoplasmosis were associated with travelling to endemic areas and visiting caves or other places inhabited by bats [3]. Thus, a thorough traveling history should be recommended in suspected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…They accumulate up to 64.1% of the cases diagnosed in immunocompetent European travelers (Staffolani et al, 2018), and concentrate 66.4% of travel-related cases belonging to a cluster. Isolated cases have been communicated in several other European countries (Ashbee et al, 2008;Doleschal et al, 2016;Lindner et al, 2018) as well as in Asia (Cho et al, 2018) and the MiddleEast (Segel et al, 2015).…”
Section: Histoplasmosis In Non-endemic Countries: the Extent Of The Pmentioning
confidence: 99%